An immune-competent, replication-permissive Syrian Hamster glioma model for evaluating Delta-24-RGD oncolytic adenovirus. Issue 11 (31st May 2021) - Phillips, Lynette M; Li, Shoudong; Gumin, Joy; Daou, Marc; Ledbetter, Daniel; Yang, Jing; Singh, Sanjay; Parker Kerrigan, Brittany C; Hossain, Anwar; Yuan, Ying; Gomez-Manzano, Candelaria; Fueyo, Juan; et al.
Abstract: Background: Oncolytic adenoviruses are promising new treatments against solid tumors, particularly for glioblastoma (GBM), and preclinical models are required to evaluate the mechanisms of efficacy. However, due to the species selectivity of adenovirus, there is currently no single animal model that supports viral replication, tumor oncolysis, and a virus-mediated immune response. To address this gap, we took advantage of the Syrian hamster to develop the first intracranial glioma model that is both adenovirus replication-permissive and immunocompetent. Methods: We generated hamster glioma stem-like cells (hamGSCs) by transforming hamster neural stem cells with hTERT, simian virus 40 large T antigen, and h-RasV12. Using a guide-screw system, we generated an intracranial tumor model in the hamster. The efficacy of the oncolytic adenovirus Delta-24-RGD was assessed by survival studies, and tumor-infiltrating lymphocytes (TILs) were evaluated by flow cytometry. Results: In vitro, hamGSCs supported viral replication and were susceptible to Delta-24-RGD mediated cell death. In vivo, hamGSCs consistently developed into highly proliferative tumors resembling high-grade glioma. Flow cytometric analysis of hamster gliomas revealed significantly increased T-cell infiltration in Delta-24-RGD infected tumors, indicative of immune activation. Treating tumor-bearing hamsters with Delta-24-RGD led to significantly increased survival compared to hamsters treated with phosphate buffered saline (PBS). Conclusions: This adenovirus-permissive, immunocompetent hamster glioma model overcomes the limitations of previous model systems and provides a novel platform to study the interactions between tumor cells, the host immune system, and oncolytic adenoviral therapy; understanding of which will be critical to implementing oncolytic adenovirus in the clinic.